CoRe database of binary neutron star merger waveforms. (13th November 2018) - Dietrich, Tim; Radice, David; Bernuzzi, Sebastiano; Zappa, Francesco; Perego, Albino; Brügmann, Bernd; Vivekanandji Chaurasia, Swami; Dudi, Reetika; Tichy, Wolfgang; Ujevic, Maximiliano
Abstract: We present the computational relativity (CoRe ) collaboration's public database of gravitational waveforms from binary neutron star mergers. The database currently contains 367 waveforms from numerical simulations that are consistent with general relativity and that employ constraint satisfying initial data in hydrodynamical equilibrium. It spans 164 physically distinct configuration with different binary parameters (total binary mass, mass-ratio, initial separation, eccentricity, and stars' spins) and simulated physics. Waveforms computed at multiple grid resolutions and extraction radii are provided for controlling numerical uncertainties. We also release an exemplary set of 18 hybrid waveforms constructed with a state-of-art effective-one-body model spanning the frequency band of advanced gravitational-wave detectors. We outline present and future applications of the database to gravitational-wave astronomy.